The Evolution of Journalism in the Digital Age: Analyzing the Impact of Social Media on News Process and Information Integrity - Sultan, Moehammad Iqbal; Amir, Andi Subhan (Universitas Mercu Buana, 2024)
The development of information technology, especially social media, has dramatically changed the journalism landscape. This study aims to analyze changes in the work process of journalists and news distribution and their implications for information integrity. Using a qualitative case study methodology with a narrative analysis approach, this research collected data through in-depth interviews with journalists and content analysis of news reports published on social media. The results indicate a significant shift in news gathering, filtering, and presentation, where speed often precedes depth of analysis. This suggests that social media has caused a change from investigative journalism to instant journalism that emphasizes speed over depth. The findings highlight a decline in fact verification and an increased risk of spreading inaccurate information. Based on these results, this study recommends developing stricter ethical guidelines and training for journalists in handling the pressures of news distribution on social media, as well as implementing new technologies that can support real-time verification of facts to strengthen the integrity of information.